Regeneration of Post-Agricultural Brownfield for Social Care Needs in Rural Community: Is There Any Transferable Experience - Klusáček, Petr; Charvátová, Klára; Navrátil, Josef; Krejčí, Tomáš; Martinát, Stanislav (International journal of environmental research and public health, 2021)
In the 21st century, rural communities face many challenges, including implications of dynamic population aging, a lack of social care services, and the occurrence of abandoned post-agricultural brownfields. This paper is methodologically based on the findings derived from a set of qualitative in-depth interviews with the key rural stakeholders, explores the decisive factors and limits, accelerators, and barriers governing successful regeneration of the post-agricultural brownfield in the post-socialist environment. We are using the case of the regeneration project of a large-scale former communist agricultural cooperative, located in Vranovice, the Czech Republic, to illuminate how complex and challenging the redevelopment of a post-agricultural brownfield into a social care facility for elderly people is. A wide agreement among the experts in the field of community development exists that this regeneration project can serve as a model example for other rural municipalities that are sharing similar local development issues. Our findings illustrate how important and challenging at the same time are the matters of good governance, the active and long-term participation of stakeholders in the regeneration project, and the real-life introduction of the public-private partnership concept, particularly in immensely transforming the post-socialist countryside.
Keywords: Rural Population; zemědělství; Public-Private Sector Partnerships; venkovské obyvatelstvo; Humans; Social Support; senioři; Česká republika; Czech Republic; Aged; partnerství veřejného a soukromého sektoru; Agriculture; sociální opora; lidé